Impact Analysis of Dwell Angles on Current Shape and Torque in Switched Reluctance Motors - Syeda Fatima Ghousia (Institute of Advanced Engineering and Science, 2012)
The reduction of torque ripple is the main target in research for designing a variable drive system with switched reluctance motors (SRM) for higher torque density and better efficiency. This ripple is due to the transition of excitation current between the adjacent phases. Precise control of turn-on and turn off angle is required to smooth the torque. In this paper, the effects of selecting the turn-on and turn-off angles are simulated in detail. It is observed that with the extended turn-on and turn off angles, the precise selection of turn-on and turn off angle can alter the shape of the excitation current in the stator coil and its point of overlapping with the adjacent coil. Therefore the transition between different phases can be smoothed out. The impact of this alteration on the excitation current and torque ripple as a function of different parameters of dwell angle is studied in detail in this paper. It is found that a sinusoidal current shape can also be obtained with the proper selection of these parameters.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.236